2010
DOI: 10.1111/j.1741-3729.2009.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Facilitator and Facilitation Characteristics on Participants' Ratings of Stepfamily Education

Abstract: We examine the relative importance of facilitator and facilitation characteristics on participant ratings of a stepfamily education program. Data from 48 facilitators and 598 participants suggest that quality facilitation is more meaningful to participants than whether facilitators have comparable demographic characteristics or life experiences. Hierarchical regressions identified time management effective use of personal experiences, and clear explanation of material as key facilitation skills. Popular assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…It would also be useful to learn what elements of teaching techniques and program materials make the marriage education content most useful and relevant to program participants. A recent study found limited evidence that characteristics of the facilitator matter for assessments of stepcouples' satisfaction with the program (Higginbotham & Myler, 2010). Understanding more about the educator's role in enhancement of target outcomes for stepcouples would be useful.…”
Section: Recommendations For Future Research and Evaluationmentioning
confidence: 98%
“…It would also be useful to learn what elements of teaching techniques and program materials make the marriage education content most useful and relevant to program participants. A recent study found limited evidence that characteristics of the facilitator matter for assessments of stepcouples' satisfaction with the program (Higginbotham & Myler, 2010). Understanding more about the educator's role in enhancement of target outcomes for stepcouples would be useful.…”
Section: Recommendations For Future Research and Evaluationmentioning
confidence: 98%
“…For example, in one evaluation, the overall rating of stepfamily education was higher for classes taught by facilitators who currently lived in a stepfamily. However, there was a negative association for facilitators who grew up in a stepfamily (Higginbotham & Myler, 2010).…”
Section: Life Experiencesmentioning
confidence: 72%
“…Several studies from this initiative have already been published (e.g., Higginbotham & Adler-Baeder, 2008;Higginbotham & Skogrand, 2010;Skogrand, Barrios-Bell, & Higginbotham, 2009). The present study builds off the article published by Higginbotham and Myler (2010) that assessed similarities between participants and facilitators and predicted overall ratings of the program. In their analyses, participants' perceptions of the facilitators' facilitation abilities were used as predictor variables.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations